Unlocking the potential for digital mental health technologies in the UK: a Delphi exercise. Issue 1 (January 2020) - Murphy, Clare; Thorpe, Lucy; Trefusis, Harriet; Kousoulis, Antonis
Abstract : Background: Digitally enabled services can contribute to the support, treatment and prevention of mental health difficulties; however, questions remain regarding how we can most usefully harness such technology in primary and secondary mental healthcare settings. Aims: To identify barriers and facilitators to enable the potential of digital mental health in England, Scotland, Wales and Northern Ireland. Method: A three-round Delphi exercise was carried out online with 16 participants from across the four nations of the UK representing the following stakeholder groups: service providers, health professionals, policymakers, lived experience, small and medium enterprises and academics. Qualitative data were collected in the first round (80 fragments) that were then coded to produce a 26-item round-two questionnaire for participant rating. Participants were given the opportunity to reconsider their scores in light of the group responses in round three. Results: Eight statements under the following five themes reached consensus with median scores between 8 and 10 (i.e. important/very important): co-production; the human element; data security; funding; and regulation. Conclusions: The Delphi process allowed consensus to be achieved regarding the factors that experts consider important for harnessing technology in primary and secondary mental healthcare. Knowledge of these factors can help users and providers of mental health services negotiate how best to move forward with digitally enabled systems of care.